Pengalaman Parental burnout pada Ibu Tunggal dalam Struktur Generasi Sandwich - Zahra Firnando; Dwi Indah Aktori; Audiva Zaskia Refinka; Betesda Bernadeta Nazara; Atila Alfa Reza; Nurhayati .; Suci Ramadhani; Agitia Kurniati Asrila (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Single mothers within the sandwich generation structure are required to meet the needs of two generations simultaneously, placing them at heightened risk of experiencing parental burnout, yet research that specifically examines the intersection of these two phenomena remains relatively limited, particularly in Indonesia. This study aims to explore the experience of parental burnout among single mothers within the sandwich generation structure. Using a qualitative approach with a phenomenological type, data were analyzed through Interpretative Phenomenological Analysis (IPA). Two single mothers who act as primary breadwinners and sole caregivers participated in this study. The results revealed three main themes: (1) Motivation to Persist, (2) Challenges and Caregiving Pressures, and (3) Exhaustion and Coping Strategies. The parental burnout experienced aligned with the four dimensions of the Parental Burnout Assessment (PBA), with role exhaustion being the most dominant dimension. The factors contributing to burnout were analyzed using Ecological Systems Theory, which showed that burnout is driven by multi-level pressures across the micro, meso, exo, and macro systems, stemming from a chronic imbalance between high caregiving demands and limited resources. Nevertheless, religious and relational coping strategies help participants maintain their daily functioning.